2020
DOI: 10.1186/s13041-020-00582-9
|View full text |Cite
|
Sign up to set email alerts
|

BDNF impact on synaptic dynamics: extra or intracellular long-term release differently regulates cultured hippocampal synapses

Abstract: Brain Derived Neurotrophic Factor (BDNF) signalling contributes to the formation, maturation and plasticity of Central Nervous System (CNS) synapses. Acute exposure of cultured brain circuits to BDNF leads to up-regulation of glutamatergic neuro-transmission, by the accurate tuning of pre and post synaptic features, leading to structural and functional synaptic changes. Chronic BDNF treatment has been comparatively less investigated, besides it may represent a therapeutic option to obtain rescue of post-injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 112 publications
0
38
0
Order By: Relevance
“…This neuroplastic effect is probably achieved through the activation of intracellular-signaling cascades [ 173 , 174 ]. Recent data suggest that intracellular overexpression of BDNF in hippocampal developing neurons induces maturation of excitatory and inhibitory synapses, with respect to exogenous application of BDNF [ 175 ]. BDNF mice lacking BDNF die during the second postnatal week [ 176 ] and BDNF deficit causes inhibition of dendritic arborization [ 92 , 177 ] and reduction of expression of genes functionally related to vesicular trafficking and synaptic communication [ 178 ].…”
Section: Neuroplasticity In Mdd: the Effects Of Antidepressant Thementioning
confidence: 99%
“…This neuroplastic effect is probably achieved through the activation of intracellular-signaling cascades [ 173 , 174 ]. Recent data suggest that intracellular overexpression of BDNF in hippocampal developing neurons induces maturation of excitatory and inhibitory synapses, with respect to exogenous application of BDNF [ 175 ]. BDNF mice lacking BDNF die during the second postnatal week [ 176 ] and BDNF deficit causes inhibition of dendritic arborization [ 92 , 177 ] and reduction of expression of genes functionally related to vesicular trafficking and synaptic communication [ 178 ].…”
Section: Neuroplasticity In Mdd: the Effects Of Antidepressant Thementioning
confidence: 99%
“…In mouse Alzheimer’s disease (AD), elevated levels of H3k9me1 [51, 128] leads to the downregulation of BDNF (brain-derived neurotrophic factor). BDNF is critical for neuronal synaptic plasticity [98] as well as mediator of neuronal differentiation and cognitive functions [88]. Moreover, GRN is co-transported with BDNF within neuronal axon and dendrites [92].…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the role of chronic BDNF exposure was observed in glutamatergic neurons in organotypic hippocampal culture. Rauti et al treated hippocampal slices with BDNF (250 ng/mL) for 72 h and observed increases in spine density and synapse number in pyramidal neurons in the hippocampus [ 41 ]. Furthermore, BDNF intracellular overexpression in hippocampal neurons increases both the frequency and the amplitude of the excitatory synapses, therefore indicating the relevance of BDNF [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rauti et al treated hippocampal slices with BDNF (250 ng/mL) for 72 h and observed increases in spine density and synapse number in pyramidal neurons in the hippocampus [ 41 ]. Furthermore, BDNF intracellular overexpression in hippocampal neurons increases both the frequency and the amplitude of the excitatory synapses, therefore indicating the relevance of BDNF [ 41 ]. Therefore, in the present study, we demonstrated that the activation of BKB2R by the specific agonists NG291 and BK can become an important tool in the fight against Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%